2020
DOI: 10.1002/rcm.8945
|View full text |Cite
|
Sign up to set email alerts
|

In vitro reactions of a cyanocobalamin–cisplatin conjugate with nucleoside monophosphates

Abstract: Rationale Cisplatin (CP) is a widely used anticancer drug characterized by toxic side effects that could be alleviated using novel delivery systems including CP prodrugs. The in vitro incubation of a putative prodrug, obtained from cyanocobalamin (CNCbl) and cis‐diamminemonochloroplatinum(II) (mCP), with nucleoside monophosphates (NMPs) was investigated. Methods The in vitro reactions between the putative prodrug CNCbl‐mCP and the NMPs of adenosine (AMP), guanosine (GMP), cytidine (CMP) and uridine (UMP) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…By using CblCN as a carrier, inorganic cytostatic agents can also be selectively accumulated in cancer cells, so that the side effects of traditional chemotherapy are significantly reduced. For obvious reasons, most of the studies reported have focused on cisplatin and related complexes [ 23 , 25 , 26 , 27 , 31 , 32 ]. Efficient inhibition of DNA replication and transcription abilities, requires a drug release within the cell that is enabled by CN bridging, which is prone to the action of both intracellular enzymes [ 23 ] and visible light inducing photo-decay of the cobalt-carbon bond [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…By using CblCN as a carrier, inorganic cytostatic agents can also be selectively accumulated in cancer cells, so that the side effects of traditional chemotherapy are significantly reduced. For obvious reasons, most of the studies reported have focused on cisplatin and related complexes [ 23 , 25 , 26 , 27 , 31 , 32 ]. Efficient inhibition of DNA replication and transcription abilities, requires a drug release within the cell that is enabled by CN bridging, which is prone to the action of both intracellular enzymes [ 23 ] and visible light inducing photo-decay of the cobalt-carbon bond [ 33 ].…”
Section: Introductionmentioning
confidence: 99%